The rendement of boiled water extract of mature leaves of mangrove Sonneratia alba (JURNAL PERIKANAN DAN KELAUTAN TROPIS, 2020)
Sonneratia alba is a mangrove that is found in North Sulawesi and has been known to contain bioactive substances through researches. Rendement is the ratio of the dry weight of the extract to the amount of the raw material. Rendement value is related to the amount of bioactive content contained. The higher the rendement, the higher the bioactive componds contain in sample. The purpose of this study was to obtain the rendement value of Sonneratia alba leaves extract taken from Wori Village, North Minahasa Regency, North Sulawesi Province which was extracted using the infundation method with extraction time of 10 minutes, 20 minutes, 30 minutes, 40 minutes, 50 minutes at boiling water solvent. Sample comparison of 50 gr : 3000 mL solvent (1:60 w / v). The results showed the lowest rendement in the 10 minutes treatment was 18.34% and the highest was in the 50 minutes treatment 29.76%. The rendement of leaves extract of this study has the possibility of qualitatively containing bioactive compounds that can act as antibacterial and antioxidant. Overall, it can be concluded that the extraction time affects the rendement, where the longer the extraction time, the higher the rendement.Key words: Rendement, Sonneratia alba, old leaf, infundation AbstrakSonneratia alba merupakan salah satu jenis mangrove yang banyak di temukan di Sulawesi Utara dan sudah dikenal mengandung zat-zat bioaktif melalui hasil-hasil penelitian. Rendemen adalah perbandingan berat kering ekstrak dengan jumlah bahan baku. Nilai rendemen berkaitan dengan banyaknya kandungan bioaktif yang terkandung. Semakin tinggi rendemen maka semakin tinggi kandungan zat yang tertarik ada pada suatu bahan baku. Tujuan dari penelitian ini adalah mendapatkan rendemen ekstrak daun tua Sonneratia alba yang diambil dari Desa Wori, Kabupaten Minahasa Utara, Provinsi Sulawesi Utara yang diesktrak menggunakan metode infundasi dengan waktu ekstraksi yaitu 10 menit, 20 menit, 30 menit, 40 menit, 50 menit pada pelarut air mendidih. Perbandingan sampel 50 gr : 3000 mL pelarut (1:60 b/v). Hasil penelitian menunjukkan nilai rendemen terendah pada perlakuan 10 menit yakni 18,34% dan tertinggi pada perlakuan 50 menit 29,76%. Rendemen ekstrak daun tua penelitian ini memiliki kemungkinan secara kualitatif mengandung senyawa bioaktif yang dapat berperan sebagai antibakteri dan antioksidan. Secara keseluruhan disimpulkan bahwa lama waktu ekstraksi berpengaruh terhadap rendemen, dimana semakin lama waktu ekstraksi maka semakin tinggi rendemen.Kata kunci : Rendemen, Sonneratia alba, daun tua, infundasi